A poesia como hermenêutica da vida : o sensacionismo de Fernando Pessoa sob a análise religiosa da arte de Paul Tillich - Moura, Ivanilton Aragão de (2021)
The purpose of the work is to analyze the aesthetic project of the poet Fernando (António Nogueira) Pessoa (1888-1935) under the theoretical reference of Paul (Johannes Oskar) Tillich (1886-1965), with regard to his religious analysis of art. Based on a phenomenology of meaning consciousness, Tillich understands culture and religion as functions of human creative action. In this conceptual framework, the notion of style is decisive for the understanding (analytical-hermeneutics) of the religious character of a work of art. In the light of this perspective, we seek to examine the aesthetic project of Pessoa's sensationism, highlighting such aspects and their critical relations with regard to the status of modernity. Sensationism is understood as the theoretical elaboration that ended up guiding the directions of Pessoa's work and offering the conceptual support of all its heteronyms, within the context of the first modernist generation of Portuguese literature. Sensationist aesthetics are marked by the appreciation of sensory stimuli, having the concept of sensation as a way of apprehending reality and mediating our relationship with the world. To the poet, art is constituted as an interpretation of life and sensation is the nucleus around which this hermeneutical understanding of art and existence is organized through poetic form. The first chapter is dedicated to clarifying the constitutive relations between religion, culture, art and literature, without forgetting to situate the cultural and philosophical context that dialogues with artistic production and gives it profound meanings. The second chapter presents the sensationist theory, from its official appearance within the publications of Orpheu magazine to its implications in the way in which Pessoa developed his poetry. In the third chapter, the tillichian concepts of courage, anxiety and despair became parameters to guide the analysis of the aesthetic profile of the main heteronyms as elements that denounce the existence of an implicit religious style. The analysis led us to consider how Pessoa‘s poetry not only presents itself as a way of interpreting human existential dilemmas but also expresses the impetus for religious self-transcendence.